Antagonism and Antibiofilm Activity of Sterile Microbiota Growth Medium against Klebsiella pneumoniae In Vitro - Barkat Ali Khan; Muhammad Azhar Ud Din; Mohammed Talab Mohammed; Maimoona Batool; Habib ullah (World Journal of Experimental Biosciences, 2025)
The metabolic bacteria extraction, Sterile Microbiota Growth Medium (SMGM), may play a role as an antibacterial and antibiofilm agent, reducing the virulence of pathogenic bacteria in vitro and in vivo. These extracts can be used to treat infections caused by antibiotic-resistant bacterial isolates. The present study aims to investigate the antibacterial and antibiofilm effects of SMGM extracted from non-Staphylococcus aureus growth media on the virulence of Klebsiella pneumoniae, as assessed by biofilm formation and bacterial growth rate. In the current study, 25 skin swabs were collected from healthy volunteers to isolate non-S. aureus isolates (S. epidermidis). From these isolates, SMGMs were prepared aseptically from 10 isolates of S. epidermidis by collecting the overnight growth (Nutrient broth) and preparing cell-free growth media after centrifugation and passing through Millipore filters. The microdilution method on a microtiter plate was used to evaluate the antibacterial effect of SMGM. Moreover, the microtiter plate and crystal violate method was used to assess the antibiofilm effect of different dilution of SMGM on the ability of K. pneumoniea to form biofilm in vitro. The results showed that all dilutions of SMGM ½, ¼, 1/8, 1/16, 1/32, and 1/64 reduced biofilm formation of K. pneumoniae (P
Keywords: Antibiofilm, Antagonism, Biofilm, Klebsiella pneumoniae, Microbiome